Is Stock Price Rounded for Economic Reasons in the Chinese Market - HE, Yan (Institutional Knowledge at Singapore Management University, 2006)
This paper investigates whether trading and quoting prices are rounded for both economic and cultural reasons on the Shanghai and Shenzhen Stock Exchanges in China. We find that the close, bid, and ask prices of domestic shares are rounded to the nearest 10s and 5s for economic reasons, and the last decimal point of prices clusters on 8 for cultural reasons. The cross-sectional variation in 10-cent and 5-cent rounding can be well explained by price and inverse of square root of trading volume, whereas the clustering on 8 can hardly be ascribed to economic variables. The cross-sectional variation in execution costs can be ascribed to both economic variables and rounding frequencies. In addition, the prices of foreign shares traded on the Shenzhen Stock Exchange are clustered on 10s and 5s, but not on 8. [Copyright 2006 Elsevier]